Nitrogen‐14 NMR Spectroscopic Detection of Explosophores in Solution. Issue 2 (2nd December 2015) - McAteer, Daniel; Akhavan, Jacqueline
Abstract: Nitrogen‐14 ( 14 N) quadrupolar nuclear magnetic resonance (NMR) spectroscopy was used to detect and measure the chemical environment of various nitrogen nuclei located within the explosophore of many commonly studied explosives in solution (Figure 1 ). The values are presented here as a resource for researchers in the field who may find use in this non‐destructive and convenient analytical technique. Abstract :